Anti-gender mobilizations, religion and politics: an Italian case study - Prearo, Massimo (Routledge studies in religion and politics, 2024)
"This book presents an innovative exploration of the rise of political forces that have coalesced around the anti-gender movement, shaping strategies that advocate novel intersections of religion, politicization of gender and sexuality, and radical and populist rejuvenation of conservative ideologies. Through an extensive examination of activist discourses and mobilizations, the author offers a comprehensive political analysis of anti-gender mobilization, encompassing a multidimensional examination of religious, activist, and political opportunity structures. This study unveils three distinct facets characterizing these emerging (Catholic) movements: their relative autonomy from the Church (extra-ecclesiastical), their divergence from conventional religious frameworks (extra-Catholic), and their party-political alignment within the far-right area. The author proposes a new perspective on this burgeoning Catholic cause, contextualizing it within the transnational dynamics underscored by the existing literature. Particularly noteworthy is the scrutiny of internal reshaping within the Italian political Catholicism realm between the 1990s and the 2000s set against the backdrop of the dissolution of the Christian Democratic Party. Through the lens of the Italian landscape, this study extends its analysis to offer broader insights into the contemporary political uses of religion within democracies, along with contentious issues arising from gender and sexuality debates, transcending the confines of the Italian context. This book holds significant relevance for scholars and students engaged in gender studies, religious studies, social movements, populism, political science, political sociology, political history, and Italian studies"--